Association between myopia and amplitude of accommodation in young adults - Ng, Sok Lin (2001)
To describe the association between amplitude of accommodation and refractive error as well as to evaluate the risk factors associated with myopia among medical and nursing students from School of Medical Sciences, Universiti Sains Malaysia. A total of 110 medical and nursing students with both eyes classified into the same refractive state namely emmetropia, low myopia and moderate to high myopia were enrolled in this study. The sample was randomly selected from the population with the stratified random sampling method. Refractive error, near point distance and far point distance were measured. Each eye of each subject was tested separately. The amplitude of accommodation was calculated by subtracting the far point (in diopters) from the near point (in diopter). Data analyzes was performed using SPSS software. Myopes were defined as those with refractive error of -0.75 diopter or more, have lower accommodative amplitudes (p=O.Ol2). Family history of myopia (p=0.002) and race (p=0.021) were other risk factors associated with myopia. Those with family history of myopia are at higher risk of getting myopia (odds ratio 4.4, p=0.002). After multivariate logistic regression analysis adjusting for various relevant variables, lower amplitude of accommodation (p=0.009) and family history of myopia (p=0.002) remained associated with myopia. Myopes with early onset myopia were related to higher degree of myopia (p=0.005). Early onset myopic subjects are at 5.1 times greater risk of getting higher degree of myopia (odds ratio= 5.1, p=0.005). Conclusions: This study demonstrates that lower amplitude of accommodation along with family history of myopia is important risk factors associated with myopia. On the other hand, the early onset of myopia is the risk factor for higher degree of myopia.